Evaluasi Usability pada Aplikasi Perbankan Jenius dengan Metode Usability Testing - Khairien Nissa; Hanifah Muslimah Az-Zahra; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In an increasingly competitive business world to gain profit, the National Pension Savings Bank (BTPN) provides the best service that can support its financial needs, one of which is the Jenius Banking Application. Jenius Banking application is a service that helps users to conduct financial activities such as saving, doi transaction, or sharing to safer and more attractive appearance, but found problems related to usability obtained through observation and interviews regarding the application of the interface setting features that are less precise and words that are not common to the users, therefore, research needs to be done with three steps, being the first step is evaluation conducted to measure the aspects of usability, which are learnability, efficiency, errors with the method of Usability Testing and satisfaction with LEMtool - Measuring Emotions in the Visual Interface and found 7 problems out of 10 the task scenarios are tested, the second step is provide design improvement recommendations given to user behaviorthe, results of interviews and guidelines, the third is evaluate the design solution with the first design to compare the results between the two. Application recommendations given provide an increase in learning ability metrics from 64% to 87%, an increase in the efficiency of metrics from 0.02 goals / second to 0.05 goals / second, a reduction in error metrics from 30% to 6% and an increase in existing metrics satisfaction from 56% to 84%.